Institutional investors and corporate governance - Baums, Theodor; Buxbaum, Richard M.; Hopt, Klaus J., 1940- (W. de Gruyter, 1993)
The volume contains 23 articles by international experts, both scholars and practioners dealing with the development of institutional investors (such as banks, insurances, investment companies, pension funds etc.), their investment and voting policies, the impact on managements of the companies concerned and related issues. The consequences of the international development on capital markets as well as policy implications for the respective national legislations are treated.